What older adults want from their health care providers - Hazel Williams-Roberts; Sylvia Abonyi; Julie Kryzanowski (The Beryl Institute, 2018)
Changing demographic trends and population needs have increased demand for chronic complex care and contributed to rising health care costs. The study sought to identify unmet health care needs of older adults and opportunities for service improvement in a high need suburban neighborhood of a prairie province. The insights provided by older adults informed the service design for a new model of integrated care in community settings. Narrative inquiry methodology was used to understand care experiences through stories. Stories of older adults' health care journeys were elicited with semi-structured interviews. A paradigmatic approach to analysis was applied with holistic coding, mapping of story elements followed by comparison and theming across participants' stories. Older adults perceived that relationship and informational continuity fostered effective communication and supported coordination of care. Timely access to care was valued and flexibility in types of medical encounters was suggested as an option to improve provider responsiveness. Access to information about community resources was limited and older adults required support with navigation. Structural (e.g. availability of services and transportation), financial and personal barriers exist for older adults to access and use community health services. Health care transitions were inadequately supported by comprehensive discharge planning, timely communication and follow up post discharge. New models of care need to embrace person-centred and goal directed approaches to the delivery of care to improve patient experience. Older adults offer valuable perspectives as community partners and co-designers of systems change in efforts to re-engineer health services.